2022
DOI: 10.1161/circimaging.121.013526
|View full text |Cite
|
Sign up to set email alerts
|

Breast Arterial Calcification: a Novel Cardiovascular Risk Enhancer Among Postmenopausal Women

Abstract: Background: Breast arterial calcification (BAC), a common incidental finding in mammography, has been shown to be associated with angiographic coronary artery disease and cardiovascular disease (CVD) outcomes. We aimed to (1) examine the association of BAC presence and quantity with hard atherosclerotic CVD (ASCVD) and global CVD; (2) ascertain model calibration, discrimination and reclassification of ASCVD risk; (3) assess the joint effect of BAC presence and 10-year pooled cohorts equations risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
(63 reference statements)
2
27
1
Order By: Relevance
“…After a mean follow-up of 6.5 years, BAC presence was associated with an increased risk of atherosclerotic CVD events (hazard ratio, 1.51; 95% CI, 1.13-2.20) and global CVD (HR, 1.23; 95% CI, 1.002-1.52) after controlling for the traditional CVD risk factors. Atherosclerotic CVD was a composite outcome comprising acute myocardial infarction, ischemic stroke, or CVD death, and global CVD was a composite outcome comprising ischemic heart disease, cerebrovascular disease, heart failure, cardiomyopathy, deep vein thrombosis/pulmonary embolism, cardiac arrest, peripheral vascular disease, retinal vascular occlusion, and CVD death 11 . In addition, our results are consistent with prior retrospective studies.…”
Section: Discussionsupporting
confidence: 90%
“…After a mean follow-up of 6.5 years, BAC presence was associated with an increased risk of atherosclerotic CVD events (hazard ratio, 1.51; 95% CI, 1.13-2.20) and global CVD (HR, 1.23; 95% CI, 1.002-1.52) after controlling for the traditional CVD risk factors. Atherosclerotic CVD was a composite outcome comprising acute myocardial infarction, ischemic stroke, or CVD death, and global CVD was a composite outcome comprising ischemic heart disease, cerebrovascular disease, heart failure, cardiomyopathy, deep vein thrombosis/pulmonary embolism, cardiac arrest, peripheral vascular disease, retinal vascular occlusion, and CVD death 11 . In addition, our results are consistent with prior retrospective studies.…”
Section: Discussionsupporting
confidence: 90%
“…We did not have any data to understand the quantity of BAC and its association with CVD. Albeit, one study in our synthesis reported by [21] noted that there was a threshold effect of BAC above the 95 th centile being strongly predictive of CVD, which points further studies in the direction of developing a robust and relevant scoring system for BAC beyond presence or absence on mammography. Second, the association of BAC and CVD could have been merely incidental, with no causality proven in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Three studies were cohorts, and patients were enrolled prospectively [18]- [20]. Three studies were conducted longitudinally, two prospective [21], [22] and one retrospective [23]. Reference [23] Reference [22] Reference [20] Reference [18] Reference [19] Reference [21] Study The odds of developing CVD among BAC+ participants were 1.32 (95% CI: 1.08-1.60) (22), 2.29 (95% CI: 1.40-3.74) (18), and 2.54 (95% CI: 1.03-6.30) (20) in a prospective longitudinal cohort and two prospective cohorts, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New research shows that in postmenopausal women, detecting breast arterial calcification on breast mammograms is associated with a higher risk of cardiovascular disease. The findings were published in Circulation: Cardiovascular Imaging 1 …”
mentioning
confidence: 95%